Preparing and Promoting Women for Leadership Positions in Radiology and the Imaging Industry. Issue 6 (November 2020) - Rofsky, Neil M.; Meltzer, Carolyn; Chertoff, Jocelyn D.; Gilbreath, Rachel; Canon, Cheri L.
Abstract : Abstract: A dearth of women leaders in the field of radiology and affiliated industries persists despite a recognition of the importance, value, and impact that would derive from its rectification. A targeted educational collaboration, described herein, was established between academia and industry to address this deficit and to facilitate the placement of highly qualified women into leadership positions. The actionable platform offered has the potential to narrow the gap for underrepresented groups in professional leadership positions.